Effect of sodium-glucose cotransporter-2 (SGLT2) inhibitors on serum urate levels in patients with and without diabetes: a systematic review and meta-regression of 43 randomized controlled trials. (March 2022) - Yip, Alicia Swee Yan; Leong, Shariel; Teo, Yao Hao; Teo, Yao Neng; Syn, Nicholas L. X.; See, Ray Meng; Wee, Caitlin Fern; Chong, Elliot Yeung; Lee, Chi-Hang; Chan, Mark Y.; Yeo, Tiong-Cheng; Wong, Raymond C. C.; et al.
Objectives: Sodium-glucose cotransporter-2 (SGLT2) inhibitors have been found to reduce serum urate in patients with type 2 diabetes mellitus. To evaluate if this effect applies to both patients with and without diabetes, we conducted a systematic review and meta-analysis of SGLT2 inhibitors on serum urate levels in this population. Methods: Four electronic databases (PubMed, Embase, Cochrane and SCOPUS) were searched on 25 September 2021 for articles published from 1 January 2000 up to 25 September 2021, for studies that examined the effect of SGLT2 inhibitors on serum urate in study subjects. Random-effects meta-analysis was performed, with subgroup analyses on the type of SGLT2 inhibitor agent administered, presence of type 2 diabetes mellitus, presence of chronic kidney disease and drug dose. Results: A total of 43 randomized controlled trials, with a combined cohort of 31, 921 patients, were included. Both patients with [−31.48 μmol/L; 95% confidence interval (CI): −37.35 to −25.60] and without diabetes (−91.38 μmol/L; 95% CI: −126.53 to −56.24) on SGLT2 inhibitors had significantly lower urate levels when compared with placebo. This treatment effect was similarly observed across different types of SGLT2 inhibitors. However, in type 2 diabetes mellitus (T2DM) patients with chronic kidney disease, the reduction in serum urate with SGLT2 inhibitors became insignificant (95% CI: −22.17 to 5.94, p  < 0.01). Conclusion: This study demonstrated that SGLT2 inhibitors are beneficial in reducing serum urate in patients with and without diabetes. SGLT2 inhibitors could therefore contribute to the general treatment of hyperuricaemia.